2017
DOI: 10.1002/anie.201701481
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of a Dimeric Thymol Derivative Isolated from Arnica sachalinensis

Abstract: The total synthesis of a dimeric thymol derivative (thymarnicol) isolated from Arnica sachalinensis was accomplished in 6 steps. A key biomimetic Diels-Alder dimerization was found to occur at ambient temperature and the final oxidative cyclization occurs when the substrate is exposed to air and visible light. These results indicate that this natural product is likely the result of spontaneous (non-enzyme-mediated) reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Column chromatography followed by preparative HPLC could then be used to access analytically pure samples of thymarnicol (1;4 0mgp repared so far), but still as an unavoidable mixture of the two lactol epimers.Crystallization from acetonitrile resulted in crystals suitable for single-crystal X-ray diffraction studies. [10] Thec rystal structure obtained matched that reported for the natural material, [1b] which consists of just one lactol epimer (Scheme 2). Nevertheless, subsequent analysis of these crystals by solution-phase 1 HNMR spectroscopy showed the presence of both lactol epimers.Itmust be concluded that thymarnicol (1)isstereodynamic;itexists as amixture of lactol epimers in solution but can exist as asingle epimer in the solid state.T hus,asix-step total synthesis of thymarnicol (1)has been achieved, involving the formation of nine new bonds (three C À C, six C À O), three new rings,and four new stereogenic centres.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Column chromatography followed by preparative HPLC could then be used to access analytically pure samples of thymarnicol (1;4 0mgp repared so far), but still as an unavoidable mixture of the two lactol epimers.Crystallization from acetonitrile resulted in crystals suitable for single-crystal X-ray diffraction studies. [10] Thec rystal structure obtained matched that reported for the natural material, [1b] which consists of just one lactol epimer (Scheme 2). Nevertheless, subsequent analysis of these crystals by solution-phase 1 HNMR spectroscopy showed the presence of both lactol epimers.Itmust be concluded that thymarnicol (1)isstereodynamic;itexists as amixture of lactol epimers in solution but can exist as asingle epimer in the solid state.T hus,asix-step total synthesis of thymarnicol (1)has been achieved, involving the formation of nine new bonds (three C À C, six C À O), three new rings,and four new stereogenic centres.…”
supporting
confidence: 79%
“…[18] Similarly,a ttempts to cleave the MOM ethers in epoxide 18 led to the formation of bislactones 19 in high yield (Scheme 5b). [10,19] Thep redisposed nature of these rearrangements,w hich presumably occur through [1,2]-shift mechanisms (see Scheme 5), leads us to speculate that structures akin to 17 and 19 might be isolated as natural products in the future. [20] In conclusion, through our synthetic efforts,wehave been able to investigate the chemical feasibility of Passreiters suggested biosynthetic pathway for thymarnicol (1).…”
mentioning
confidence: 99%
“…Eugenol, a phenylpropanoid, can be isolated from the plant like Syzygium aromaticum [ 44 ], Eugenia caryophyllata [ 45 ], and Ocimum gratissimum L. [ 46 ]. Thymol, a phenolic monoterpenoid, can be isolated from various natural sources like T. vulgaris L. [ 43 ], O. dictamnus L. [ 41 ] and Arnica sachalinensis [ 47 ]. Geraniol, acyclic alcohol monoterpene, can be isolated from various sources like Rosa damascene [ 48 ], Cymbopogon winterianus [ 49 ], etc.…”
Section: Methodsmentioning
confidence: 99%
“…Titanium scaffold treatment protocol, to avoid particulates, autoclave sterilization followed by an ultrasonic bath for 5 min in deionized H 2 O, and then for 5 min in H 2 O 2 at 120 v / v , and again for 10 min in deionized H 2 O, was performed, as decribed by Di Silvestro et al [ 30 ]. Furthermore, to avoid alterations of the superficial layer of the scaffolds, an important factor in cell/surface interaction, particular care was taken in performing any and all manipulations of the titanium scaffolds using only plastic or pure titanium instruments.…”
Section: Methodsmentioning
confidence: 99%